Efektivitas Low-Carb Diet vs Low-Fat Diet terhadap Body Composition pada Orang dengan Obesitas: Literature Review: Efektivitas Low-Carb Diet vs Low-Fat Diet terhadap Body Composition pada Orang dengan Obesitas: Literature Review - Indriyani, Tutut Rizki; Rahmawati, Atika; Khoirunnisa, Luthfiani; Wahyurin, Izka Sofiyya (Universitas Airlangga, 2024)
Background: Obesity is still become a serious problem today. Obesity is caused by excessive adipose tissue. One of many factors that contribute to a person's obesity is food intake. Excess carbohydrate and fat intake will be stored in the form of triglycerides in adipose tissue. In the meantime, Low-Carb Diet (LCD) and Low-Fat Diet (LFD) are one of the most popular treatments on obesity. However there are many pros and cons related to each diet based on several studies. Objectives: The indicated study aims to determine the effectiveness of LCD and LFD on body composition in people with obesity. Methods: The study was conducted through journal and literature review, based on five journal publications, filtered by related keywords. In accordance to inclusion and exclusion criteria within the last ten years in Pubmed/Medline database, Science Direct, and Wiley Online Library with the keywords